2015
DOI: 10.22555/pjets.v1i1.139
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Diversification in the Karachi Stock Exchange

Abstract: Investment in stocks and expected return from such investment always comes with risk. Financial economists and financial analysts have been working for years to find ways to minimize risk. What all financial analysts believe is that creating well-diversified portfolio can minimize risk. Fama (1976), Elton & Grubber (1977), Evans & Archer (1968) and many other analysts have shown that well-diversified portfolios can actually minimize risk and have suggested the minimum number of stocks required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
1
7
0
2
Order By: Relevance
“…Alekneviciene et.al, (2012) found that in order to eliminate 98% of diversifiable risk, a naive portfolio with 22 stocks should be formed. Similar with other researches (Tang 2004;Ahuja 2011) using daily returns as the basis for calculating the standard deviation, their empirical results support the range of 20-30 stocks are enough to achieve well a diversified in portfolio.…”
Section: Empirical Results and Discussionsupporting
confidence: 82%
“…Alekneviciene et.al, (2012) found that in order to eliminate 98% of diversifiable risk, a naive portfolio with 22 stocks should be formed. Similar with other researches (Tang 2004;Ahuja 2011) using daily returns as the basis for calculating the standard deviation, their empirical results support the range of 20-30 stocks are enough to achieve well a diversified in portfolio.…”
Section: Empirical Results and Discussionsupporting
confidence: 82%
“…In Pakistan the dividend payment are considered as one of the influential factor for investors as supported by the studies and results (Nazir et al, 2010;Hunjra et al, 2014). Another study conducted in context of Pakistan concluded that to form diversified portfolio 10 stocks should be selected (Ahuja, 2015). Therefore 10 stocks were selected for the construction of portfolio and for validity of higher co moment model with an additional and more acceptable risk measure of CVaR.…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini menunjukkan bahwa komposisi jumlah saham penyusun portofolio tersebut telah mencapai optimal. Pernyataan tersebut sesuai dengan hasil penelitian yang dilakukan oleh Suqaier & Ziyud, (2011) serta Ahuja (2011). Kedua penelitian ini menyatakan bahwa penambahan saham yang semakin banyak ke dalam portofolio dapat menurunkan risiko sampai dengan titik tertentu, jika portofolio tersebut ditambahkan dengan saham lagi, tidak diperoleh penurunan risiko yang berarti, karena jumlah saham yang menyusun portofolio telah mencapai optimal.…”
Section: Tyas Aurumaa S I Made Sudanaunclassified